TIME SERIES PREDICTION USING ICA ALGORITHMS - Gorriz, Juan M.; Puntonet, Carlos G.; Salmeron, Moises; Lang, E. W. (International Journal of Computing, 2014)
In this paper we propose a new method for volatile time series forecasting using Independent Component Analysis (ICA) algorithms and Savitzky-Golay filtering as preprocessing tools. The preprocessed data will be introduce in a based radial basis functions (RBF) Artificial Neural Network (ANN) and the prediction result will be compared with the one we get without these preprocessing tools or the classical Principal Component Analysis (PCA) tool.